Being helpful and being innovative: The role of psychological meaningfulness and positive affect - Shen, Yifei; Zhang, Zhenduo; Song, Haoyang; Zheng, Junwei; Bu, Qiong (Frontiers in Psychology, 2022)
The present study is developed based on conservation of resources theory (COR) to explore the underlying mechanism and boundary condition for the relationship between helping behavior and innovative behavior. To avoid the shortages of cross-sectional data, the present study collected two-wave and multi-source data. By collecting from 193 full-time Chinese workers and 68 supervisors at two sperate time points, this study developed and examined a moderated mediation model using Mplus 7.0. The results show that helping behavior increases innovative behavior through enhancing positive affect, and psychological meaningfulness moderates the indirect relationship between helping behavior and innovative behavior through positive affect. In the condition of high psychological meaningfulness, helping behavior has a stronger indirect impact on innovative behavior through enhancing positive affect. This study enriches the literature on the outcomes of helping behavior. Moreover, this study provides several managerial implications to amplify the positive impact of helping behavior on innovative behavior. This study develops several strategies to enhance psychological meaningfulness and promote the benefits of helping behavior.